AKTIVITAS FISIK DAN TOTAL ASUPAN LEMAK TERHADAP KOMPONEN SINDROM METABOLIK PADA PEGAWAI DAN STAF POLITEKNIK KESEHATAN MANADO - Irza Ranti; Fred Rumagit; Ana Montol (Jurnal GIZIDO, 2013)
Metabolic syndrome is a group of metabolic disorders both lipid and non- lipid which isthe risk of heart disease, metabolic disorders that include abdominal obesity, atherogenicdyslipidemia hypertension, insulin resistance with or without glucose intolerance. Thepurpose of this study is to know the prevalence of the metabolic syndrome associatedwith total physical activity and fat intake on employees and polytechnic staff Manado .This study will be conducted at the Polytechnic of Health Ministry of Health Manado inMay- October 2013 . The study was a descriptive observational analytic . The populationin this study were all employees and existing staff in the polytechnic Manado. The samplesize in this study is based on a formula specified hypothesis test for a populationproportion amounted to 96 subjects.Using logistic regression analysis results Backward LR method in step 4 to show variablehigh fasting blood glucose with low HDL cholesterol and high total cholesterol is the mostinfluential variable on the incidence of metabolic syndrome.The conclusion of this study is physical activity and fat intake was not statisticallysignificant, but the subject is detected metabolic syndrome is more prevalent in subjectswho have moderate and light physical activity with dietary fat intake that exceeded therecommended dietary allowance